Designation of the General Concept of Compensation for Work in English and Lithuanian - Tekoriūtė, Aušra (Vertimo studijos, 2020)
As part of a systematic knowledge-based analysis of terms related to regulation of wages, the paper analyzes the meaning, usage, and translation of terms designating the general concept of compensation for work in English and Lithuanian. The analysis is based mainly on Chapter IX of the Labour Code of the Republic of Lithuania and its translation into English, as well as the translation of conventions of the International Labour Organization (ILO) and some other legal texts related to wages into Lithuanian. It has been established that while some English and Lithuanian terms with the general meaning of compensation for work are very similar both semantically and functionally, it is possible to trace certain smaller or greater differences between them.
Keywords: term; translation; compensation for work; Labour Code of the Republic of Lithuania